Prediksi Kebutuhan Energi Listrik Pada PT. PLN (Persero) Rayon Aek Nabara Dengan Metode Exponential Smoothing - Sarah Syahputri; Sinar Sinurat; Imam Saputra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Palm oil production with timely operations, low cost, specifications according to the order is the target of a company. PT. Inti Indosawit Subur is a company that produces fresh fruit bunches (FFB) in the form of palm oil. During its operation, this company wants maximum profit. In achieving this company goal always considers other policies such as maximizing the total product with limited raw materials, and minimizing production costs. In this case, companies often experience reduced production and have not or are not prepared to make preparations when faced with a reduced production period. To help problems faced by PT. Inti Indosawit is fertile in carrying out its business activities, a prediction is needed. The prediction in question is how much Crude Palm Oil (CPO) will be in the coming period. In order to simplify the calculation process and obtain more optimal results, the process of calculating the amount of CPO using the Moving Average Method is attempted to assist the management of PT. Inti Indosawit Subur in predicting the amount of Crude Palm Oil (CPO) so that it does not experience reduced or excessive production so that the company prepares faster actions to meet consumer demand. The application will provide the appropriate amount of CPO from each production process so that the company will be assisted in making service policies for consumers in every request.